2015
DOI: 10.1080/13547860.2015.1045324
|View full text |Cite
|
Sign up to set email alerts
|

Retirement savings investment decisions: evidence from Malaysia

Abstract: This paper investigates individual retirement savings investment choices of members of Malaysia's Employees Provident Fund (EPF). The focus is on the option available to EPF members to invest part of their savings in approved unit trusts. A survey of EPF members allows a contrast with existing empirical evidence, largely drawn from developed countries. Three significant factors are identified: perceived importance of financial advisor; financial risk tolerance and perceived plan design. Gender and marital stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The differences between males and females' financial literacy and behaviour are evident amongst young college students even after controlling for the effects of majors, class rank, work experience and age (Chen and Volpe 2002;Mottola 2013). Similarly, several studies conducted in Malaysia supported the gender gap in financial literacy and behaviour (Falahati and Paim 2011;Ibrahim et al 2010;Jamaludin and Gerrans 2015) although it is acknowledged that the results of some studies contradict this notion (Ghazali et al 2017;Loke 2015). Notwithstanding the general agreement in the empirical literature supporting men's higher financial literacy and financial behaviour than women, research on the mechanisms that explain this gender gap is rather limited (Fonseca et al 2012) and requires further investigation.…”
Section: Gender Rolementioning
confidence: 89%
“…The differences between males and females' financial literacy and behaviour are evident amongst young college students even after controlling for the effects of majors, class rank, work experience and age (Chen and Volpe 2002;Mottola 2013). Similarly, several studies conducted in Malaysia supported the gender gap in financial literacy and behaviour (Falahati and Paim 2011;Ibrahim et al 2010;Jamaludin and Gerrans 2015) although it is acknowledged that the results of some studies contradict this notion (Ghazali et al 2017;Loke 2015). Notwithstanding the general agreement in the empirical literature supporting men's higher financial literacy and financial behaviour than women, research on the mechanisms that explain this gender gap is rather limited (Fonseca et al 2012) and requires further investigation.…”
Section: Gender Rolementioning
confidence: 89%
“…Of relevance to the present investigation, we first expect to find that individuals with higher levels of risk tolerance are more likely to save for retirement and have superior pension adequacies. This is because those with a higher risk tolerance level have been shown to be more likely to save (and invest more aggressively) for retirement relative to those who are risk averse (Fisher & Anong, 2012;Jacobs-Lawson & Hershey, 2005;Jamaludin & Gerrans, 2015;Yao et al, 2005). On that basis, a risk tolerant individual can typically expect to amass a larger retirement savings nest egg.…”
Section: Psychological Influences On Saving and Pension Adequacymentioning
confidence: 99%
“…Duqi and al-Tamimi [ 16 ] state that religiosity is a prominent predictor of UAE investors’ investment in sukuk. In Jamaludin and Gerrans [ 84 ], religiosity is closely related to an individual’s decision in choosing the type of fund. The analysis of EPF investors revealed that casual and liberal Muslims prefer conventional funds, while obedient and devoted Muslims favor Islamic funds, which suggests that religion influences an individual’s mutual fund investment decision.…”
Section: Literature Reviewmentioning
confidence: 99%